The Effects of Turmeric Extract (Curcuma longa) Loaded Hidrogels in Accelerating Wound Closure - David Setyo Budi; Reny I`tishom; Alphania Rahniayu; Mohammad Fathul Qorib (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Disruption to healing process results on longer healing duration from the timeline. Povidoneiodine and tulle are common management in wound care. The advance of industry in health sector andthe availability of natural ingredients in Indonesia provide opportunities for developing alternatives forwound care. Turmeric (Curcuma longa) contains curcumin which is anti-inflammatory, antibacterial,and antioxidant; it is good for wound healing. Hydrogel nanocomplexes of carboxymethyl chitosan canmaintain moisture in wound area and protect curcumin from hydrolysis. Objective: To analyze the potentialof turmeric extract loaded hidrogels in accelerating wound closur. Method: experimental research with“post-test only control group design”. The sample consisted of 30 mice which were assigned into 5 groups.Result: All experimental groups experienced a gradual decrease in wound length. The statistical test resultsfor groups II and III showed significant advantages compared to group IV (p<0.05). Meanwhile, group Idid not have significant differences in wound closure compared to group IV on day 1 and 3 (p>0.05), but ithad significant results (p<0.05) on day 5. Conclusion: Turmeric extract loaded hidrogels can accelerate thereduction of wound length.